Konstruksi Sosial Penerapan Nilai-Nilai Pancasila Santri Mahasiswa Pondok Pesantren Al-Amien Rejomulyo Kota Kediri - Amir Syarifuddin (Spiritualita, 2021)
Islamic boarding schools as educational institutions are also responsible forpreparing students to face the demands of the times in this modern era. Ofcourse, in religious learning, students are also given insight into understandingthe values of Pancasila. For this reason, the focus of this research is: 1) What isthe process of social construction of Pancasila values for students of Al-AmienIslamic Boarding School? 2) How are the values of Pancasila for the students ofthe Al-Amien Islamic boarding school applied?This study uses a qualitative approach with the type of field research (fieldresearch). Data collection methods that researchers use in this study include themethods of observation, interviews, and documentation. And in analyzing, theresearcher uses three steps, namely data reduction, data display, then drawconclusions or verification.Based on the research conducted, the researcher can conclude that theapplication of Pancasila values. Namely: mutual tolerance, mutual respect,mutual help, doing good, is a small picture of the application of Pancasila valuesin Islamic boarding schools, which has the aim of training students in theapplication of Pancasila values while strengthening the friendship of a student,and also maintaining the integrity of the Unitary Republic of Indonesia. . Thepurpose of the research is the first to find out how the application of Pancasilavalues in the daily life of students. The second is to find out how studentsunderstand the values of Pancasila.